HUBUNGAN ANTARA NEGARA DAN GEREJA: IMPLIKASINYA TERHADAP PENYELENGGARAAN PENDIDIKAN AGAMA DAN PENDIDIKAN KEAGAMAAN - Nobert Jegalus (Institut Filsafat dan Teknologi Kreatif Ledalero, 2013)
Should we show our obedience more to the state or to the church? Of course, we must always be obedient to God, but this does not mean that such obedience makes us withdraw ourselves from being obedient to social-human institutions, such as a state. It should be noted that the state institution itself is actually a manifestation of our human social nature established by God. In their respective areas, the state and the church are two autonomous entities. However, as public institutions they are related to each other, thus to a certain extent they are not opposed to each other. In line with this view, the Indonesian government issued some regulations on religious teaching and the teaching of religions to be implemented by the community (church). In this case, the government has the obligation to support and assist educational institutions run by the church. It should be noted, however, that the government’s support and assistance should only be secondary in order not to replace, or even to cease, the educational institutions run by private sectors, such as the church Keywords: Negara, ketaatan, Gereja, ajaran religius, ajaran tentang agama, dan pemerintahan